2020
DOI: 10.25134/quagga.v12i1.2297
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Recripocal Teaching Pair Share dengan Media Gambar Terhadap Kemampuan Berpikir Kritis Siswa SMA

Abstract: Pembelajaran mengggunakan model pembelajaran Recripocal Teaching Pais Share (RTPS) dengan media gambar dapat mempengaruhi kemampuan berpikir kritis siswa. Oleh karena itu, penelitian ini merupakan quasy experimentuntuk mengetahui pengaruh kemampuan berpikir kritis siswa SMA pada topik Sistem Pencernaan Makanan dan Pernapasan dengan menggunakan pembelajaran RTPS dengan media gambar. Data yang diambil adalah kemampuan berpikir kritis yang dinilai menggunakan rubrik. Teknik analisis data menggunakan uji anacova. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…Based on the results of student responses, it can be said that the inquiry-based pictorial riddle method online can improve online learning more interesting, and make students' thinking skills develop in the concept of static fluid. So that through the use of images in this research model, students are expected to be able to develop their abilities to improve their critical thinking skills [39][40][41]. This is in accordance with research by Vieira et al who said that the results of data analysis on survey questionnaires showed that students were satisfied with the implementation of inquiry-based learning during practicum [42].…”
Section: Figure 2 Picture Of Pictorial Riddlesupporting
confidence: 85%
“…Based on the results of student responses, it can be said that the inquiry-based pictorial riddle method online can improve online learning more interesting, and make students' thinking skills develop in the concept of static fluid. So that through the use of images in this research model, students are expected to be able to develop their abilities to improve their critical thinking skills [39][40][41]. This is in accordance with research by Vieira et al who said that the results of data analysis on survey questionnaires showed that students were satisfied with the implementation of inquiry-based learning during practicum [42].…”
Section: Figure 2 Picture Of Pictorial Riddlesupporting
confidence: 85%
“…Analysis is one of the indicators included in critical thinking skills, and students must be able to make the connection between the course content and everyday life (Virtanti & Yuniastuti, 2021;Widita, et al, 2018). According to Ndae and Widyaningrum (2020), having critical thinking skills in biology learning can help students get used to facing challenges and solving problems with their own thinking. In addition, Saputri et al in the proceeding entitled Critical thinking skills profile of senior high school students in Biology learning in 2018 noted that biological science will continue to evolve rapidly, and future students will need to be able to solve increasingly complex problems.…”
Section: Resultsmentioning
confidence: 99%
“…Berpikir kritis dapat juga dianalisis dengan menggunakan kriteria atau elemen dasar yang disingkat dengan FRISCO (Focus, Reason, Inference, Situation, Clarity and Overview). Keaktifan siswa untuk menyampaikan pendapat juga salah satu dari kemampuan berpikir kritis (Ndae & Widyaningrum, 2020).…”
Section: Pembahasanunclassified